Digital content management strategies for enhancing stakeholder engagement: A communication perspective on website-based platforms - Kholik, Abdul; Rizki, Menati Fajar; Maulydia, Farah Widari; Syahdan, Mohammad Arsha; Anadyar, Arbifadhil Fikri; Zalikha, Nasya Rizqy (Privietlab, 2025)
This study examines the strategic implementation of website-based Content Management Systems (CMS) as a communication tool to enhance stakeholder engagement in digital environments. Using a qualitative research approach combined with the Multimedia Development Life Cycle (MDLC) methodology, this research analyzes the development and implementation of a digital communication platform for Nasyid Nusantara Jakarta, focusing on its effectiveness in strengthening stakeholder relationships and supporting Sustainable Development Goal 16 (Peace, Justice, and Strong Institutions). Through focus group discussions with 13 participants and a comprehensive website evaluation, the study reveals that strategic digital content management can significantly improve organizational communication effectiveness. The research findings indicate that the implemented CMS platform achieved an overall effectiveness score of 80%, demonstrating strong technical functionality (100%) and content credibility (85.2%), while identifying areas for improvement in transparency, accountability (58.8%), and interactive engagement (66.7%). This study contributes to communication theory by demonstrating how digital platforms can serve as strategic communication tools that facilitate meaningful stakeholder dialogue and community building. These findings have practical implications for organizations seeking to leverage digital communication technologies to enhance stakeholder engagement and achieve sustainable development objectives through effective content management.